Analisis Akad Dalam Bisnis Multi Level Marketing - Ahmad Ramdhani (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The purpose of writing this article is to analyze the transaction contracts that exist in the multi-level marketing business, Multi-Level Marketing is a network business that has products and it is allowed, until now there has been Sharia MLM, and has been under the auspices of DSN MUI about Sharia tiered direct sales about the processes of Sharia MLM. However, there are still many MLM business people who do not know the concept of the contract used. This research method contains data sources, data types, data collection techniques, and data analysis techniques. Based on the results of research conducted shows that in the multi-level marketing business there are several contracts, including the first recruitment system, this system uses the Wakalah Bil Ujrah Akad. The second Buying and Selling is the Akad used is Akad Bai'i (Buying and Selling) or you can use an Order contract (Akad Salam) which is the difference between the MLM business and the Money Game Business. Third Bonus Distribution, In the distribution of contract bonuses.